Calcium titanate powder and composition
Patent Information
- Application Number
- JP2025058379
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2026-10-14
AI Technical Summary
【0026】 本開示によれば、樹脂と混合したときの流動性に優れるチタン酸カルシウム粉末を提供することができる。また、流動性に優れる組成物を提供することができる。
Smart Images

Figure 2026165793000001_ABST
Abstract
Description
[Technical Field]
[0001] This disclosure relates to calcium titanate powder and compositions. [Background technology]
[0002] Calcium titanate powder is known as a ceramic filler used in resins for electronic materials and the like. Patent Document 1 describes a spherical calcium titanate powder having an average circularity of 0.80 or more, and a shear viscosity of 3000 Pa·s or less measured under specific conditions. Patent Document 1 also states that such a powder does not significantly reduce processability or workability even when densely packed into resins, and can simultaneously achieve high dielectric constant and low dielectric loss tangent. [Prior art documents] [Patent Documents]
[0003] [Patent Document 1] International Publication No. 2023 / 189965 [Overview of the Initiative] [Problems that the invention aims to solve]
[0004] This disclosure provides calcium titanate powder that exhibits excellent fluidity when mixed with resin. It also provides a composition that exhibits excellent fluidity. [Means for solving the problem]
[0005] One aspect of this disclosure provides the following calcium titanate powder.
[0006] [1] Contains multiple calcium titanate particles having a particle size of 10 μm or more, Calcium titanate powder wherein the average circularity of the plurality of calcium titanate particles is 0.87 or higher.
[0007] The calcium titanate powder described in [1] above has an average circularity of 0.87 or higher among multiple calcium titanate particles with a particle diameter of 10 μm or more. Such calcium titanate powder contains many spherical particles among the larger calcium titanate particles with a particle diameter of 10 μm or more. Here, particles with a particle diameter of 10 μm or more can be obtained by melting the raw material powder and coarsening the particles when manufacturing calcium titanate powder. Therefore, it is thought that a large portion of the calcium titanate powder obtained by melting has a spherical shape because the average circularity of particles with a particle diameter of 10 μm or more is 0.87 or higher. Such calcium titanate powder can reduce the viscosity of the composition when mixed with a resin and can improve the fluidity of the composition.
[0008] The calcium titanate powder in [1] above may also be the following [2] to [8].
[0009] [2] The calcium titanate powder according to [1], wherein the average circularity of the calcium titanate powder is 0.95 or higher.
[0010] The calcium titanate powder described in [2] above has a high average circularity, which further improves its fluidity when mixed with resin.
[0011] [3] The calcium titanate powder according to [1] or [2], wherein the volume fraction of the group of particles with a particle size of 10 μm or more, as measured by laser diffraction and scattering, is 25% or more.
[0012] The calcium titanate powder described in [3] above has a high proportion of calcium titanate particles with a particle size of 10 μm or more, resulting in a high proportion of nearly spherical calcium titanate particles, which further improves the fluidity when mixed with resin.
[0013] [4] In the volume-based particle size distribution measured by a laser diffraction / scattering method, where the particle size at which the cumulative value from the small particle size side reaches 50% of the total is defined as D50, and the particle size at which the cumulative value reaches 90% of the total is defined as D90, the D50 is 4 to 10 μm, and the D90 is 12 to 30 μm, the calcium titanate powder according to any one of [1] to [3].
[0014] In the calcium titanate powder of the above [4], both D50 and D90 are in suitable ranges, so it has further excellent fluidity when mixed with a resin.
[0015] [5] The calcium titanate powder according to [4], wherein the particle size D100 at which the cumulative value reaches 100% of the total is 80 μm or less.
[0016] In the calcium titanate powder of the above [5], D100 which is a coarse particle is not excessively large, so it has further excellent fluidity when mixed with a resin.
[0017] [6] The BET specific surface area is 2.0 m 2 / g or less, the calcium titanate powder according to any one of [1] to [5].
[0018] The calcium titanate powder of the above [6] has a small BET specific surface area. Such a calcium titanate powder is obtained by sufficiently fusing the raw material particles with each other. Accordingly, the shape of each calcium titanate particle in the calcium titanate powder becomes nearly spherical, and the fluidity when mixed with a resin is further excellent.
[0019] [7] 78 parts by mass of calcium titanate powder is blended with 22 parts by mass of a bisphenol F-type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C, and the shear viscosity measured using a rheometer at a plate temperature of 30°C and 1 rpm is 300 Pa·s or less, the calcium titanate powder according to any one of [1] to [6].
[0020] The calcium titanate powder described in [7] above, when mixed with resin to form a composition, exhibits a sufficiently low shear viscosity at a shear rate of 1 rpm. Therefore, it has excellent fluidity and workability.
[0021] [8] A calcium titanate powder according to any one of [1] to [7], wherein 22 parts by mass of a bisphenol F type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C is blended with 78 parts by mass of calcium titanate powder, and when the shear viscosity is measured using a rheometer at a plate temperature of 30°C, 1 rpm and 100 rpm, respectively, V100 / V1 is 0.1 to 0.7.
[0022] The calcium titanate powder described in [8] above has a V100 / V1 ratio of 0.1 to 0.7 in the composition when mixed with the resin. When such calcium titanate powder is mixed with the resin to form a composition, it has sufficient thixotropy and therefore exhibits an excellent balance between shear viscosity at low shear rates and shear viscosity at high shear rates. Consequently, it offers excellent workability.
[0023] One aspect of this disclosure provides the following compositions.
[0024] [9] A composition comprising the calcium titanate powder and resin described in any one of [1] to [8] above.
[0025] The composition described in [9] above contains the calcium titanate powder described in any one of [1] to [8] above. Therefore, it has excellent fluidity. [Effects of the Invention]
[0026] According to this disclosure, it is possible to provide calcium titanate powder that exhibits excellent fluidity when mixed with resin. Furthermore, it is possible to provide a composition with excellent fluidity. [Brief explanation of the drawing]
[0027] [Figure 1]This figure shows an example of a thermal spraying facility for producing calcium titanate powder using the flame melting method. [Modes for carrying out the invention]
[0028] Embodiments of this disclosure are described below. However, the following embodiments are illustrative for the purpose of illustrating this disclosure and are not intended to limit this disclosure to the following. The upper or lower limits of numerical ranges explicitly stated in this disclosure may be replaced with any of the values shown in the examples. Furthermore, the upper and lower limits described individually may be combined in any way. The symbol "~" used in numerical ranges indicates a numerical range that includes the upper and lower limits. For example, "X~Y" indicates a numerical range of "X or greater and Y or less". Unless otherwise specified, the materials or components exemplified in this disclosure may be used individually or in combination of two or more.
[0029] <Calcium titanate powder> One embodiment of calcium titanate powder contains a plurality of calcium titanate particles having a particle diameter of 10 μm or more, and the average circularity of the plurality of calcium titanate particles is 0.87 or more. In this specification, "powder" means "a collection of a plurality of particles." The calcium titanate powder may also contain a plurality of calcium titanate particles having a particle diameter of less than 10 μm.
[0030] Calcium titanate powder has an average circularity of 0.87 or higher among multiple calcium titanate particles with a particle diameter of 10 μm or more. Such calcium titanate powder contains many spherical particles among the larger particles of 10 μm or more, and can also be called spherical calcium titanate powder. The composition obtained by mixing such calcium titanate powder with a resin has excellent fluidity without an increase in viscosity. From the viewpoint of further improving the fluidity of the above composition, the average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more may be 0.89 or higher, 0.90 or higher, or 0.91 or higher.
[0031] The calcium titanate powder may have an average circularity of 0.95 or higher, or 0.96 or higher. Having an average circularity within the above range increases the proportion of nearly spherical particles in the calcium titanate powder, resulting in even better fluidity of the composition when mixed with the resin.
[0032] The circularity of calcium titanate particles can be measured using a powder image analysis device (for example, Sysmex Corporation's product name "FPIA-3000"). Specifically, calcium titanate powder is dispersed in pure water to obtain a dispersion, and this dispersion is then flowed through a planar stretchable flow cell. The calcium titanate particles moving within the cell are recorded as an image using an objective lens. The equivalent circle diameter and projected perimeter of the calcium titanate particles are determined from the recorded image, and the circularity of the particles is calculated from the following equation (1). In the following equation (1), HD represents the equivalent circle diameter, and PM represents the projected perimeter of the particle. The equivalent circle diameter means the diameter of a perfect circle with the same area as the projected area of the particle. Circularity = π × HD / PM (1)
[0033] The average circularity of the entire calcium titanate powder can be determined by taking the arithmetic mean of the circularity calculated for each image of the calcium titanate particles contained in the calcium titanate powder using the procedure described above. The number of calcium titanate particles (number of circularity data points) used to calculate the average circularity of the entire calcium titanate powder may be 200 or more (for example, 200) from the viewpoint of ensuring sufficiently high measurement accuracy. The range of this number of calcium titanate particles may be, for example, 200 to 100,000.
[0034] The average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more can be determined by extracting images of particles with an equivalent circle diameter HD of 10 μm or more from the images of calcium titanate particles used to calculate the circularity described above. That is, the average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more can be determined by taking the arithmetic mean of the circularity calculated for each of the extracted images of calcium titanate particles with an equivalent circle diameter HD of 10 μm or more. The number of calcium titanate particles (number of circularity data points) used to determine this average circularity may be the same as when determining the average circularity of the entire calcium titanate powder. When calculating the average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more, "particle diameter of 10 μm or more" means that the equivalent circle diameter HD is 10 μm or more.
[0035] When calculating the average circularity of multiple calcium titanate particles having a particle diameter of 10 μm or more, the number of particles with an equivalent circle diameter HD of 10 μm or more may be 100 or more, or 200 or more, from the viewpoint of ensuring sufficiently high measurement accuracy. The range of the number of images of particles with an equivalent circle diameter HD of 10 μm or more may be, for example, 100 to 1000.
[0036] In calcium titanate powder, the volume fraction of particles with a particle diameter of 10 μm or more, as measured by laser diffraction / scattering, may be 25% or more, 26% or more, or 27% or more. The above particle group may be a group of calcium titanate particles. When the volume fraction of the group of calcium titanate particles with a particle diameter of 10 μm or more is within the above range, the proportion of nearly spherical particles in the calcium titanate powder increases, resulting in even better fluidity when mixed with resin. The above volume fraction may be 40% or less, or 35% or less. The above volume fraction range may be, for example, 25-40% or 27-35%.
[0037] In the volume-based particle size distribution of calcium titanate powder measured by laser diffraction / scattering, D50 is defined as the particle size when the cumulative value from smallest particle size reaches 50% of the total, and D90 is defined as the particle size when the cumulative value reaches 90% of the total. D50 may be 4-10 μm, 5-9 μm, or 5-8 μm, and D90 may be 12-30 μm, 14-25 μm, or 16-20 μm. Calcium titanate powder with D50 and D90 within the above ranges exhibits superior fluidity when mixed with resin, as both D50 and D90 are within suitable ranges.
[0038] When the cumulative value mentioned above reaches 10% of the total, the particle size D10 may be 1-5 μm, 2-4 μm, or 2-3 μm. Having D10 within these ranges results in even better fluidity when mixed with the resin.
[0039] The particle size D100 when the above cumulative value reaches 100% of the total may be 80 μm or less, or 75 μm or less. Calcium titanate powder with D100 within the above range exhibits superior fluidity when mixed with resin because D100 is not too large. D100 may be 60 μm or larger. The range of D100 may be, for example, 60 to 75 μm, or 60 to 80 μm.
[0040] Laser diffraction and scattering methods can be used for measurement in accordance with the method described in JIS Z 8825:2013 "Particle size analysis - Laser diffraction and scattering methods". A laser diffraction particle size analyzer (manufactured by Microtrac Bell Co., Ltd., product name "MT3300EXII") can be used for measurement.
[0041] The BET specific surface area of calcium titanate powder is 2.0 m². 2 / g or less, 1.5m 2 Less than / g, or 1.2m 2It may be less than / g. Calcium titanate powder with a BET specific surface area within the above range is obtained by sufficient melting of the raw material particles. Therefore, the shape of each calcium titanate particle in the calcium titanate powder becomes closer to spherical. Such calcium titanate powder exhibits even greater fluidity when mixed with resin. The BET specific surface area is 0.2 m². 2 / g or more, or 0.5m 2 It may be greater than or equal to / g. The BET specific surface area range is, for example, 0.2 to 2.0 m². 2 / g, or 0.5~1.2m 2 The value may be / g. The BET specific surface area can be measured, for example, by the BET single-point method using nitrogen gas adsorption with a specific surface area measuring device (e.g., Mountec Co., Ltd., product name "MACSORB").
[0042] The relative permittivity of calcium titanate powder may be 80 or less, 70 or less, or 50 or less. The relative permittivity of calcium titanate powder may be 20 or more. The range of relative permittivity of calcium titanate powder may be, for example, 20 to 80, 20 to 70, or 20 to 60. The dielectric loss tangent of calcium titanate powder may be 0.010 or less, 0.009 or less, 0.008 or less, or 0.006 or less. The dielectric loss tangent of calcium titanate powder may be 0.001 or more. The range of dielectric loss tangent of calcium titanate powder may be 0.001 to 0.010, 0.001 to 0.009, or 0.001 to 0.008. The insulating properties of calcium titanate powder are improved when the relative permittivity and dielectric loss tangent are within the above ranges. Specifically, the relative permittivity and dielectric loss tangent can be determined by the method described in the examples.
[0043] The carbon content of the calcium titanate powder may be 0.005 to 0.03% by mass, 0.007 to 0.025% by mass, or 0.01 to 0.02% by mass. The carbon content can be measured by the method described in the examples. The measurement of the carbon content may be performed after washing the calcium titanate powder by the method described in the examples.
[0044] When 22 parts by mass of bisphenol F type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C is blended with 78 parts by mass of calcium titanate powder, and the shear viscosities measured using a rheometer at a plate temperature of 30°C, 1 rpm, and 100 rpm are denoted as V1 and V100, respectively, the V100 / V1 ratio may be 0.1 to 0.7, 0.2 to 0.6, or 0.2 to 0.5. A composition containing calcium titanate powder and resin with V100 / V1 within the above range has sufficient thixotropy and an excellent balance between shear viscosity at low shear rates and shear viscosity at high shear rates. Therefore, it has excellent workability.
[0045] V1 may be 300 Pa·s or less, 200 Pa·s or less, or 150 Pa·s. When such calcium titanate powder is mixed with a resin to form a composition, the shear viscosity at a shear rate of 1 rpm is sufficiently low. Therefore, it has even better fluidity. V1 may be 20 Pa·s or more, or 40 Pa·s or more. The range of V1 may be, for example, 20 to 300 Pa·s, or 40 to 150 Pa·s.
[0046] V100 may be 1 to 100 Pa·s, 10 to 50 Pa·s, or 20 to 40 Pa·s. Compositions containing calcium titanate powder and resin in which V100 is within the above range exhibit even better fluidity and workability.
[0047] Examples of bisphenol F type epoxy resins include "Epicote 807" manufactured by Mitsubishi Chemical Corporation. Examples of rheometers include "Modular Compact Rheometer MCR 102" manufactured by Anton Paar. A conical cone (3 degrees) is used as the rotating rod of the rheometer.
[0048] The method for producing calcium titanate powder in this disclosure is described below. The method for producing calcium titanate powder includes a step of spheroidizing a raw material powder containing calcium titanate powder by a powder melting method.
[0049] The raw material powder may be amorphous calcium titanate powder. The raw material powder may have an average particle size (D50) of 1-30 μm, 2-10 μm, or 2-5 μm, from the viewpoint of the average particle size of the powder after spheroidization and the ease of handling or feeding the raw material powder. The average circularity of the raw material powder is not particularly limited. For example, "CT-3" (product name) manufactured by Kyoritsu Material Co., Ltd. can be used as the raw material powder.
[0050] The method for preparing the raw material powder is not particularly limited. For example, bulk powder of calcium titanate obtained by reacting titanium dioxide (TiO2) and calcium carbonate (CaCO3) under high-temperature conditions may be used as the raw material powder, or calcium titanate powder prepared by a wet process may be used as the raw material powder. From the viewpoint of ease of availability and cost reduction, calcium titanate powder prepared by a solid-phase process may be used as the raw material powder.
[0051] From the viewpoint of reducing dielectric loss tangent and ensuring the reliability of electronic materials, the raw material powder may contain impurities such as alkali metal elements like Li, Na, and K, metal elements like Fe, and anions like Cl and Br, with a content of 0.01% by mass or less.
[0052] A method for producing calcium titanate powder includes a step of spheroidizing the raw material powder using a powder melting method. The powder melting method is a method of heating the raw material powder to a high temperature above its melting point, and may be a method of spheroidizing it using a flame melting method in which the raw material powder is introduced into a flame and melted. In the flame melting method, by adjusting the thermal energy applied to the raw material powder, the average circularity of multiple calcium titanate particles having a particle diameter of 10 μm or more in the calcium titanate powder can be made 0.87 or higher.
[0053] The thermal energy added to the raw material powder can be adjusted, as described later, for example, by adjusting the ratio of the flow rate of the supplied combustible gas to the amount of raw material powder supplied, and the ratio of the flow rate of the supplied combustible gas to the flow rate of the auxiliary combustion gas.
[0054] Flow rate of the combustible gas to be supplied (m³3 / h) and the feed rate of the raw material powder (kg / h) (combustible gas / raw material ratio: m 3 / kg) is, from the viewpoint of applying sufficient thermal energy to the raw material powder to sufficiently melt the raw material powder, 0.2 (m 3 / kg) or more, or 0.5 (m 3 / kg) or more. The combustible gas / raw material ratio is, from the viewpoints of reducing thermal energy, suppressing re-melting of the obtained calcium titanate particles having a particle diameter of 10 μm or more, and improving the average circularity, 2.0 (m 3 / kg) or less, 1.5 (m 3 / kg) or less, or 1.2 (m 3 / kg) or less. The range of the combustible gas / raw material ratio may be, for example, 0.2 to 2.0 (m 3 / kg), 0.5 to 1.5 (m 3 / kg), or 0.5 to 1.2 (m 3 / kg).
[0055] The ratio of the flow rate of the supplied combustible gas to the flow rate of the combustion-supporting gas (combustible gas / combustion-supporting gas ratio) may be 0.05 or more, or 0.12 or more, from the viewpoint of sufficiently forming a flame to promote melting of the raw material powder and improving the average circularity of the calcium titanate particles having a particle diameter of 10 μm or more. The combustible gas / combustion-supporting gas ratio may be 0.25 or less, or 0.20 or less, from the viewpoint of suppressing the flame from becoming excessively large, preventing re-melting of the calcium titanate particles, and improving the average circularity. The range of the combustible gas / combustion-supporting gas ratio may be, for example, 0.05 to 0.25, or 0.12 to 0.20.
[0056] As the combustible gas, for example, one or a mixture of two or more of acetylene, propane, butane, etc. may be used. The mixed gas may be, for example, LPG. The combustion-supporting gas may be a gas containing oxygen. From the viewpoint of facilitating combustion of the combustible gas, reducing the generation of conductive soot (carbon), and improving the insulating property of the obtained calcium titanate powder, the oxygen-containing gas may be pure oxygen having a purity of 99% by mass or more. From the viewpoint of reducing the calorific value of the gas, an inert gas such as air or argon may be mixed into the combustion-supporting gas.
[0057] Figure 1 shows an example of a thermal spraying facility for producing calcium titanate powder by flame melting. The thermal spraying facility 100 is equipped with a burner 11 and a melting furnace 12. The burner 11 is connected to a combustible gas supply pipe 16, a combustion-supporting gas supply pipe 17, and a raw material supply pipe 18. The raw material powder, which is fed into the melting furnace 12 through the raw material supply pipe 18, is melted by the flame 19 generated from the burner 11. As a result, the raw material powder particles fuse together and their shape is refined, and calcium titanate powder can be obtained in which the average circularity of the calcium titanate particles with a particle size of 10 μm or more is 0.87 or more. The calcium titanate powder containing the obtained calcium titanate particles can be sucked up by a blower 15 and recovered in a bag filter 14 through piping 13.
[0058] The melting furnace 12 is not limited to a vertical furnace body, but may also be a horizontal furnace or inclined furnace, which is horizontal in which the flame is blown out horizontally. The atmosphere inside the melting furnace 12 may be an environment with a high oxygen partial pressure from the viewpoint of suppressing the reduction of the raw material powder. The raw material powder supplied into the melting furnace 12 through the raw material supply pipe 18 may be supplied as powder, or it may be supplied in a slurry state in which the raw material powder is dispersed in water or alcohol.
[0059] The combustible gas may be supplied by the combustible gas supply pipe 16, and the auxiliary combustion gas may be supplied by the auxiliary combustion gas supply pipe 17. The flame 19 generated from the burner 11 may be formed using, for example, LPG as the combustible gas and oxygen as the auxiliary combustion gas. Note that the thermal spraying equipment is not limited to that shown in Figure 1.
[0060] The method for producing calcium titanate powder may include, as necessary, other steps after the step of spheroidizing the raw material powder by a powder melting method. Other steps include drying the obtained calcium titanate powder, crushing it, and classifying it. In the drying step, the heating temperature may be 1250°C or lower. As the drying apparatus, for example, an electric furnace or a gas furnace can be used. The heating time may be 1 to 24 hours, 1 to 12 hours, or 1 to 4 hours.
[0061] The crushing step may be performed if the obtained calcium titanate powder is in the form of aggregates. The crushing step may be carried out by methods such as using an agate mortar and pestle, a ball mill, a vibratory mill, a jet mill, or a wet jet mill. Crushing may be carried out dry, or it may be carried out wet by mixing with a liquid such as water or alcohol. In wet crushing, calcium titanate powder can be obtained by drying after crushing. Examples of drying methods include heat drying, vacuum drying, freeze drying, and supercritical carbon dioxide drying.
[0062] The classification process may be performed to obtain calcium titanate powder having a desired average particle size (D50). Examples of classification methods include sieving, liquid cyclone, and wind classification.
[0063] Furthermore, the method for producing calcium titanate powder may include a step of surface treatment of the obtained calcium titanate powder, a washing step to reduce impurities in the calcium titanate powder, and so on.
[0064] <Composition> A composition according to one embodiment comprises the above-mentioned calcium titanate powder and a resin. Because such a composition contains the above-mentioned calcium titanate powder, it has high fluidity and excellent workability. The content of calcium titanate powder in the composition may be 50 to 90% by mass, or 65 to 80% by mass, from the viewpoint of achieving both fluidity and insulating properties of the resin.
[0065] The resin may include at least one resin selected from thermoplastic resins or thermosetting resins. Examples of resins include polyethylene resins, polypropylene resins, epoxy resins, silicone resins, phenolic resins, melamine resins, urea resins, unsaturated polyester resins, fluororesins, polyamide resins such as polyimide resins, polyamideimide resins, and polyetherimide resins, polyester resins such as polybutylene terephthalate resins and polyethylene terephthalate resins, polyphenylene sulfide resins, all aromatic polyester resins, polysulfone resins, liquid crystal polymer resins, polyethersulfone resins, polycarbonate resins, maleimide-modified resins, ABS resins, AAS (acrylonitrile-acrylic rubber-styrene) resins, AES (acrylonitrile-ethylene-propylene-diene rubber-styrene) resins, hydrocarbon elastomer resins, polyphenylene ether resins, aromatic polyene resins, etc. These may be used individually or in combination of two or more.
[0066] The composition may also contain a curing agent, a curing accelerator, a mold release agent, a coupling agent, a coloring agent, a flame retardant, and an ion scavenger, etc.
[0067] The composition can be manufactured by blending the calcium titanate powder and resin described above in a predetermined ratio and mixing them. Mixing equipment such as a sieve, a three-roll mill, a ball mill, and a planetary mixer can be used. These devices may be used in appropriate combinations.
[0068] Although several embodiments of this disclosure have been described above, this disclosure is not limited to the above embodiments. For example, the calcium titanate powder may contain other trace components besides calcium titanate. Furthermore, the calcium titanate powder may be surface-treated with a silane coupling agent or the like. [Examples]
[0069] The contents of this disclosure will be explained in more detail below with reference to examples and comparative examples. However, this disclosure is not limited to the examples described below.
[0070] <Manufacturing of calcium titanate powder> (Example 1) Using a thermal spraying apparatus as shown in Figure 1, the combustible gas supplied from the combustible gas supply pipe 16 to the burner 11 was LPG, and the auxiliary gas supplied from the auxiliary gas supply pipe 17 to the burner 11 was oxygen. Calcium titanate powder (manufactured by Kyoritsu Material Co., Ltd., trade name "CT-3", hereinafter referred to as "raw material powder") was melted in a flame to obtain the calcium titanate powder of Example 1. Note that the flow rate of the supplied combustible gas (m³) 3 The ratio of the supply rate of raw material powder (kg / h) to the amount of combustible gas (combustible gas / raw material) is 0.9 (m 3 ( / kg) and the flow rate of the combustible gas to be supplied and the flow rate of the auxiliary gas (m 3 The ratio (combustible gas / combustible gas ratio) was set to 0.16.
[0071] (Comparative Example 1) A commercially available raw material powder, similar to that used in Example 1, was prepared. This was used as the calcium titanate powder for Comparative Example 1.
[0072] (Examples 2-5, Comparative Examples 2,3) Except for changing the combustible gas / raw material ratio and the combustible gas / auxiliary gas ratio as shown in Table 1, calcium titanate powder was flame-melted in the same procedure as in Example 1 to obtain the calcium titanate powders of Examples 2-5 and Comparative Examples 2 and 3.
[0073] <Evaluation of calcium titanate powder> The average circularity, particle size distribution, BET specific surface area, relative permittivity, dielectric loss tangent, and carbon content of each calcium titanate powder obtained in each example and comparative example were determined according to the following procedure. Furthermore, evaluation resin compositions were prepared using each calcium titanate powder according to the following procedure, and their shear viscosity was measured.
[0074] [Measurement of average circularity] The average circularity of each calcium titanate powder was measured using a powder image analyzer (Sysmex Corporation, product name "FPIA-3000") following the procedure below. Calcium titanate powder was dispersed in pure water to obtain a dispersion. This dispersion was then flowed into a planar stretchable flow cell, and the calcium titanate particles moving within the cell were recorded as images using an objective lens. From the recorded images, the equivalent circle diameter and projected perimeter of the calcium titanate particles were determined, and the circularity of the particles was calculated using the following equation (1). In equation (1), HD represents the equivalent circle diameter, and PM represents the projected perimeter of the particle. The average circularity of 200 arbitrary particles was calculated from the image of the entire calcium titanate powder and used as the average circularity of the entire calcium titanate powder. The results are shown in "Average Circularity" in Table 1. Circularity = π × HD / PM (1)
[0075] Furthermore, from the image of the entire calcium titanate powder as described above, images of particles with an equivalent circle diameter (HD) of 10 μm or more were extracted. The number of extracted particles with an equivalent circle diameter (HD) of 10 μm or more was 100 or more. The circularity was calculated for each image of the extracted particles with an equivalent circle diameter (HD) of 10 μm or more, and the average circularity of multiple calcium titanate particles with a particle diameter of 10 μm or more was calculated. The results are shown in Table 1, "Average Circularity of Particles with a Diameter of 10 μm or More".
[0076] [Particle size distribution measurement] The particle size distribution of each calcium titanate powder was measured using a laser diffraction particle size analyzer (Microtrac Bell Co., Ltd., product name "MT3300EXII"). The samples were taken in 80 cm³ glass beakers. 3Pure water and 0.1 g of calcium titanate powder were added and dispersed for 1 minute using an ultrasonic homogenizer (Sonics & Materials, product name "Vibra Cell", model number VC505). The dispersed calcium titanate powder was then added drop by drop using a dropper to a laser diffraction particle size distribution analyzer, and measurements were taken 30 seconds after the predetermined amount was added. The particle size distribution was calculated from the light intensity distribution data of the diffraction / scattered light of the calcium titanate powder detected by the sensor in the laser diffraction particle size distribution analyzer.
[0077] In the obtained particle size distribution, the particle size at which the cumulative value from smallest particle size reached 10% of the total was defined as D10, the particle size at which the cumulative value reached 50% was defined as D50, the particle size at which the cumulative value reached 90% was defined as D90, and the particle size at which the cumulative value reached 100% was defined as D100. D10, D50, D90, and D100 were calculated separately. In addition, the volume fraction of the particle group with a particle size of 10 μm or larger was calculated. The results are shown in Table 1.
[0078] [BET specific surface area measurement] The specific surface area (BET) of each calcium titanate powder was determined using a specific surface area analyzer (Mountec Co., Ltd., product name "MACSORB") by the single-point BET method with nitrogen gas adsorption. Nitrogen gas was used as the adsorption gas, and helium gas was used as the carrier gas. The measurement was performed after drying and degassing 1.1 to 1.4 g of calcium titanate powder at 300°C for 30 minutes. The results are shown in Table 1.
[0079] [Measurement of dielectric properties (relative permittivity and dielectric loss tangent)] The dielectric properties of each calcium titanate powder were measured using a powder dielectric constant analyzer (manufactured by Keycom Co., Ltd., product name "TM Cavity Resonator" (cylindrical cavity resonance method)). PTFE resin cell (cylindrical, volume 1154 cm³) was used. 3 After filling the device with 2.5 to 3.0 g of calcium titanate powder and setting it in the apparatus, the resonance peak at 1 GHz was read, and the relative permittivity and dielectric loss tangent were measured. The results are shown in Table 1.
[0080] [Measurement of carbon content] The carbon content (mass%) in 0.3 g of each calcium titanate powder was measured using a carbon / sulfur simultaneous analyzer (LECO, product name "CS-444LS") and quantified using the calibration curve method. The results are shown in Table 1.
[0081] Next, the carbon content of each calcium titanate powder after washing was determined using the following procedure. 3 g of calcium titanate powder was added to 37 g of acetone and stirred for 30 minutes to obtain a slurry. This slurry was then treated with a centrifuge at 3500 rpm for 10 minutes to separate the calcium titanate powder from the acetone, and the supernatant liquid of the acetone was discarded. This washing operation with acetone was repeated twice, and the washed calcium titanate powder was dried at 120°C for 2 hours. The carbon content (mass%) in 0.3 g of the washed calcium titanate powder was measured using a carbon / sulfur simultaneous analyzer (LECO, product name "CS-444LS") and quantified using the calibration curve method. The results are shown in Table 1.
[0082] [Shear viscosity measurement] An evaluation resin composition was obtained by mixing calcium titanate powder with a liquid bisphenol F type epoxy resin (manufactured by Mitsubishi Chemical Corporation, trade name "Epicoat 807") having a kinematic viscosity of 40 mPa·s at 25°C, so that each calcium titanate powder content was 78% by mass. The evaluation composition obtained using the calcium titanate powder of Comparative Example 1 solidified, making it impossible to measure its shear viscosity. The evaluation resin compositions obtained using the calcium titanate powders of Examples 1-5 and Comparative Examples 2 and 3 were measured at a measurement temperature of 30°C using a rheometer equipped with a conical cone (3 degrees) (manufactured by Anton Paar, trade name "Modular Compact Rheometer MCR 102"), measuring the shear viscosity V1 (Pa·s) at a shear rate of 1 (1 / s) and the shear viscosity V100 (Pa·s) at a shear rate of 100 (1 / s). V100 / V1 was calculated using the measured viscosities. The results are shown in Table 1.
[0083] [Table 1]
[0084] As shown in Table 1, the calcium titanate powders of Examples 1 to 5, in which the average circularity of multiple calcium titanate particles having a particle size of 10 μm or more was 0.87 or higher, were confirmed to have reduced viscosity and excellent fluidity when mixed with resin. [Industrial applicability]
[0085] According to this disclosure, it is possible to provide calcium titanate powder that exhibits excellent fluidity when mixed with resin. Furthermore, it is possible to provide a composition with excellent fluidity. [Explanation of Symbols]
[0086] 100... Thermal spraying equipment, 11... Burner, 12... Melting furnace, 13... Piping, 14... Bag filter, 15... Blower, 16... Combustible gas supply pipe, 17... Combustible gas supply pipe, 18... Raw material supply pipe, 19... Flame.
Claims
1. It contains multiple calcium titanate particles having a particle size of 10 μm or more. Calcium titanate powder wherein the average circularity of the plurality of calcium titanate particles is 0.87 or higher.
2. The calcium titanate powder according to claim 1, wherein the average circularity of the entire calcium titanate powder is 0.95 or higher.
3. The calcium titanate powder according to claim 1 or 2, wherein the volume fraction of the group of particles with a particle size of 10 μm or more, as measured by laser diffraction and scattering, is 25% or more.
4. Calcium titanate powder according to claim 1 or 2, wherein, in a volume-based particle size distribution measured by laser diffraction / scattering, the particle size when the cumulative value from smallest particle size reaches 50% of the total is defined as D50, and the particle size when the cumulative value reaches 90% of the total is defined as D90, wherein D50 is 4 to 10 μm and D90 is 12 to 30 μm.
5. The calcium titanate powder according to claim 4, wherein the particle size D100 when the cumulative value reaches 100% of the total is 80 μm or less.
6. BET specific surface area is 2.0 m² 2 The calcium titanate powder according to claim 1 or 2, wherein the amount is less than or equal to / g.
7. The calcium titanate powder according to claim 1 or 2, comprising 78 parts by mass of calcium titanate powder and 22 parts by mass of bisphenol F type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C, wherein the shear viscosity measured using a rheometer at a plate temperature of 30°C and 1 rpm is 300 Pa·s or less.
8. The calcium titanate powder according to claim 1 or 2, wherein 22 parts by mass of bisphenol F type epoxy resin having a kinematic viscosity of 40 mPa·s at 25°C are blended with 78 parts by mass of calcium titanate powder, and when the shear viscosity is measured using a rheometer at a plate temperature of 30°C, 1 rpm and 100 rpm, respectively, V100 / V1 is 0.1 to 0.
7.
9. A composition comprising the calcium titanate powder and resin described in claim 1 or 2.
Citation Information
Patent Citations
Spherical calcium titanate powder and resin composition using same
WO2023189965A1